Komposisi Asam Lemak dan Kadar Malondialdehida Daging Itik Lokal yang diberi Antioksidan Alami - Lestari, D.; Rukmiasih; Suryati, T.; Hardjosworo, P. S.; Lase, J. A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Cihateup duck is one of the local Indonesian poultry from West Java. These ducks are raised inTasikmalaya and Garut. Cihateup duck has the potential to produce meat, but duck meat has beenconsidered to have off-odor. components off-odor formed when the fatty acids are oxidized. A studywith the aim to protect unsaturated fatty acids in local duck meat from oxidation using Pluchea indicaLess (beluntas) and Cosmos caudatus (kenikir) in feed as the source of natural antioxidants. The studyused was complete randomized design (RAL) with 7 treatments and 5 replications. The treatment wasPluchea indica Less or Cosmos caudatus powder with the duration of administration 1, 2 or 3 weeksbefore the age of harvest (10 weeks). Ducks used were 35 heads of Cihateup duck. Variables observedwere moisture content, fat content, Malondialdehyde (MDA), composition of fatty acid, and sensorycharacteristic of duck meat. The results showed that the effect of Pluchea indica Less or Cosmos caudatuswere not significant on moisture content and fat content. The effect of Pluchea indica Less or Cosmoscaudatus on MDA, composition of fatty acid, and and off-odor intensities of duck meat during cookingwas significantly different (P<0.05). It was concluded that this addition of Pluchea indica Less for 3 weeksor Cosmos caudatus for 2 weeks could lower off-odor on local duck meat.